Նապոլեոնյան մեծ կնիքը. իշխանության խորհրդանիշերը - Ֆահրադյան, Սիրանուշ («Նաիրի» հրատ.)
In 1947, Matenadaran‟s Department for Preservation and Research of Archival Documents received Napoleon I Bonapart‟s handwritten decree to Pierre Chambaud, Knight of the Legion of Honor, bearing a seal with Napoleon‟s imperial coat of arms. The study of the seal allows us not only to confirm the authenticity of the document (the primary objective) and to identify the author, but also to explore traditional and new combinations of symbolic images in the formation of the Napoleonic era. It is worth mentioning that the new heraldry was designed to recreate the use of symbols of the medieval society, without isolating itself from the previous eras. These new changes gave rise to new structures and practices that are beyond conventional heraldry by also bearing social, cultural and aesthetic significance. Eventually, the new heraldry gradually entered the public consciousness and became part of its ideology and psychology. Thus, it is associated not only with the Emperor, but also with the French identity in general. В 1947 году в отдел Хранения и научной обработки архивных документов Институтa древних рукописей имени Месропа Маштоца “Матенадаран” поступил рукописный указ, выданный Наполеоном I Бонапартом Рыцарю Почетного легиона Пьеру Шамбо, который сопровождается печатью с имераторским гербом Наполеона. Изучение печати позволяет не только подтвердить подлинность документа, что является основной целью исследования, но и определить автора, а также изучить традиционные и новые комбинации символических образов в наполеоновскую эпоху. Новая эмблематика наполеоновских времен, не будучи изолированной от предыдущих эпох, была разработана с целью воссоздания символического опыта средневекового общества. Эти изменения породили новые структуры, которые выходят за пределы геральдики, приобретают общее социальное, культурное и эстетическое значение. В итоге, эмблематические коды, содержащие символы наполеоновской власти, постепенно проникли в общественное сознание, став мировоззрением и психологией. Они стали ассоциироваться не только с императором, но и с французской идентичностью как таковой.
Keywords: Մատենադարանի հավաքածու; Պատմագիտություն; Ֆրանսիա